Effect of phosphoric fertilizers as a source of sulphur on malt barley total and technological grain yields - J. Potarzycki; W. Grzebisz (Plant, Soil and Environment, 2007)
Malt barley production requires a technology increasing nitrogen use efficiency, because of a high sensitivity of barley total grain yield and quality parameters to external growth factors. In the conducted study an effect of two P fertilizers on the background of N application on total and technological grain yields were studied. The highest total grain yield was harvested on plots fertilized with 60 kg N/ha, irrespective of the P fertilizer type. However, the technological grain yield showed a high year-to-year variability; the highest was recorded in 2001 on the plot fertilized with 60 kg N/ha and the P-PAPR fertilizer. The N and S concentrations and N:S ratios in immature grains at harvest were used to evaluate both yield types. Nitrogen concentration in the final total yield allowed making yields prognosis with the highest probability. The maximum yields of technological malt barley were attainable provided that total S concentration in immature grains at harvest was above 0.23% and the N:S ratio was narrower than 8.0.